TNIK-driven regulation of ERK5 transcriptional activity in endothelial cells - Samanthapudi, Venkata Subrahmanya Kumar; Kotla, Sivareddy; Le, Nhat-Tu (Frontiers in Cardiovascular Medicine, 2025)
Extracellular signal-regulated kinase 5 (ERK5) is essential for cardiovascular development and endothelial cell (EC) function. Activation of ERK5 through MEK5-mediated phosphorylation at threonine 218 and tyrosine 220 (T218/Y220) drives the transcriptional activation of myocyte enhancer factor-2 (MEF2), promoting the expression of KLF2 and KLF4—key transcription factors that maintain vascular homeostasis. We previously demonstrated that ponatinib suppresses ERK5 transcriptional activity without affecting laminar-flow (l-flow)-induced T218/Y220 phosphorylation, suggesting a non-canonical regulatory mechanism. Since ponatinib inhibits Traf2- and Nck-interacting kinase (TNIK), we hypothesized that TNIK modulates ERK5 transcriptional activity. Using a mammalian one-hybrid assay and quantitative RT-PCR (qRT-PCR), we show that TNIK knockdown reduces ERK5 transcriptional activity and downregulates KLF2, KLF4, and eNOS expression, whereas TNIK overexpression enhances ERK5 transcriptional activity. Constitutively active MEK5 (CA-MEK5α) rescues ERK5 transcriptional activity in TNIK-depleted cells, but TNIK overexpression fails to overcome inhibition by dominant-negative MEK5 (DN-MEK5), indicating a MEK5-dependent mechanism. Moreover, phosphorylation-deficient TNIK mutants (S764A and S769A) retain the ability to enhance ERK5 transcriptional activity, suggesting a kinase-independent regulatory role. TNIK knockdown also increases NFκB activity and EC apoptosis, linking TNIK to the regulation of inflammatory and survival pathways. These findings identify TNIK as a novel modulator of ERK5 signaling through both MEK5-dependent and independent mechanisms, highlighting its potential as a therapeutic target for vascular inflammation and endothelial dysfunction.